MED27 Variants Cause Developmental Delay, Dystonia, and Cerebellar Hypoplasia. Issue 4 (8th February 2021) - Meng, Linyan; Isohanni, Pirjo; Shao, Yunru; Graham, Brett H.; Hickey, Scott E.; Brooks, Stephanie; Suomalainen, Anu; Joset, Pascal; Steindl, Katharina; Rauch, Anita; Hackenberg, Annette; High, Frances A.; et al.
Abstract : The Mediator multiprotein complex functions as a regulator of RNA polymerase II–catalyzed gene transcription. In this study, exome sequencing detected biallelic putative disease‐causing variants in MED27, encoding Mediator complex subunit 27, in 16 patients from 11 families with a novel neurodevelopmental syndrome. Patient phenotypes are highly homogeneous, including global developmental delay, intellectual disability, axial hypotonia with distal spasticity, dystonic movements, and cerebellar hypoplasia. Seizures and cataracts were noted in severely affected individuals. Identification of multiple patients with biallelic MED27 variants supports the critical role of MED27 in normal human neural development, particularly for the cerebellum. ANN NEUROL 2021;89:828–833